Emerging Trends in Sustainable Biological Resources and Bioeconomy for Food Production - Luis A. Trujillo-Cayado; Rosa M. Sánchez-García; Irene García-Domínguez; Azahara Rodríguez-Luna; Elena Hurtado-Fernández; Jenifer Santos (Applied Sciences)
The mounting global population and the challenges posed by climate change underline the need for sustainable food production systems. This review synthesizes evidence for a dual-track bioeconomy, green (terrestrial plants and insects) and blue (aquatic algae), as complementary pathways toward sustainable nutrition. A comprehensive review of the extant literature, technical reports, and policy documents published between 2015 and 2025 was conducted, with a particular focus on environmental, nutritional, and techno-economic metrics. In addition, precision agriculture datasets, gene-editing breakthroughs, and circular biorefinery case studies were extracted and compared. As demonstrated in this study, the use of green resources, such as legumes, oilseeds, and edible insects, results in a significant reduction in greenhouse gas emissions, land use, and water footprints compared with conventional livestock production. In addition, these alternative protein sources offer substantial benefits in terms of bioactive lipids. Blue resources, centered on micro- and macroalgae, furnish additional proteins, long-chain polyunsaturated fatty acids, and antioxidant pigments and sequester carbon on non-arable or wastewater substrates. The transition to bio-based resources is facilitated by technological innovations, such as gene editing and advanced extraction methods, which promote the efficient valorization of agricultural residues. In conclusion, the study strongly suggests that policy support be expedited and that research into bioeconomy technologies be increased to ensure the sustainable meeting of future food demands.